2011
DOI: 10.3801/iafss.fss.10-599
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Evacuation Times from Lecture Theatre Type Rooms Using a Network Model

Abstract: This paper presents a series of trial evacuations from several university campus lecture theatres. The results from the trial evacuations are compared against simulations using a Monte Carlo network evacuation model. Data from a number of literature sources from lecture theatre type rooms is then used to further compare the predictions from the model. Results show that the model gives reasonable predictions when the constrictions provided by either the exit doors or the aisle widths are accounted for. The incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…10 The duration of evacuation can be calculated a variety of methods from simple manual calculations to complex statistical models. 11 According to a comprehensive literature review, the authors found that no statistical machine learning models have been employed yet to forecast the duration of emergency evacuation during hospital fires. 5 Therefore, in this study, machine learning models were used to predict the duration of hospital emergency evacuation during fire.…”
mentioning
confidence: 99%
“…10 The duration of evacuation can be calculated a variety of methods from simple manual calculations to complex statistical models. 11 According to a comprehensive literature review, the authors found that no statistical machine learning models have been employed yet to forecast the duration of emergency evacuation during hospital fires. 5 Therefore, in this study, machine learning models were used to predict the duration of hospital emergency evacuation during fire.…”
mentioning
confidence: 99%